Gap State Finance Law In General Services Agency Regional (Blud) The Potential To Cause Corruption Crime - Risky Eko Novi Artanto; Amin Purnawan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
This research is motivated persistence of financial irregularities in the management of Public Service Agency (BLUD) in the form of illegal action by way of irregularities contained in the establishment and administration of the managerial incentives that resulted in financial losses of any element of State. The purpose of this study is to analyze and explain the legal gaps in the State Treasury General Services Agency (BLUD) potentially Corruption. The method used in this paper qualitative descriptive case study case number Sprin. Evidence/ 314 / IV / 2018 / Reskrimsus, with normative juridical approach. Based on this research, that the financial legal gaps in the State Public Service Agency, which is used by the perpetrators of corruption is a way of cutting managerial remuneration or incentive structural officials Fiscal of 2014-2016 conducted by the offender, resulting in state losses of Rp. 4227319755.Keywords: Legal Loopholes; Public Finance; Corruption.